2015
DOI: 10.1002/bdra.23401
|View full text |Cite
|
Sign up to set email alerts
|

Sensory neuron differentiation potential of in utero mesenchymal stem cell transplantation in rat fetuses with spina bifida aperta

Abstract: Our results indicate that the transplantation of MSCs into the spinal cord could promote the transplanted MSCs and the surrounding cells to differentiate toward a sensory neuron cell fate and to play an important role in protecting sensory neurons in DRG. This approach might be of value in the treatment of sensory neuron deficiency in spina bifida aperta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…As deficiencies resulting from NTDs are found in the neural tissue, skin, muscle, and skeleton, BMSCs with multi-lineage differentiation potential could facilitate the repair of multiple tissue damages resulting from NTDs. Indeed, our previous studies have shown that BMSCs directly injected into the fetal spinal column differentiated into nerve and muscle cells, secreted growth factors, and reduced neural apoptosis 20 24 . Nevertheless, direct cell injection into neural tissue is not only a technical challenge but also poses a risk of trauma to the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…As deficiencies resulting from NTDs are found in the neural tissue, skin, muscle, and skeleton, BMSCs with multi-lineage differentiation potential could facilitate the repair of multiple tissue damages resulting from NTDs. Indeed, our previous studies have shown that BMSCs directly injected into the fetal spinal column differentiated into nerve and muscle cells, secreted growth factors, and reduced neural apoptosis 20 24 . Nevertheless, direct cell injection into neural tissue is not only a technical challenge but also poses a risk of trauma to the fetus.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the included studies, such as type and source of stem cells, animal models and available outcomes, are shown in Table 1 30–55 . Most studies used MSCs (77%, 20/26), with the placenta, amniotic fluid and bone marrow as the source of cells.…”
Section: Resultsmentioning
confidence: 99%
“…In small animal models, injection of adult rat BM‐MSCs at E16 into the spinal cord of retinoic acid generated fetal rats with MMC, was associated with a reduction in spinal cord cell death assessed by TUNEL analysis at E20 (death cells; 4.8 ± 0.3% vs. 8.9 ± 0.6%, p < 0.05), 34 and an increase in the number of sensory neurons in the dorsal root ganglion (33.4 ± 1.9% vs. 25.3 ± 1.6%, p < 0.01) 35 . The intervention also improved corticospinal tract communication to the anterior tibialis muscle, demonstrated by a rise in motor evoked potentials (0.26 ± 0.02 mV vs. 0.18 ± 0.02 mV, p < 0.05) and a shorter latency period (22.8 ± 0.3 ms vs. 25.4 ± 0.8 ms, p < 0.05) 38 …”
Section: Efficacy Of Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to the multipotentiality of MSCs, they can possibly be used to treat a variety of conditions. In rats, MSCs injected into the spinal cord of fetuses, which were induced to have spina bifida by the administration of retinoic acid, engrafted and expressed markers of motor neurons, neurons, sensory neurons, and neural precursor cells while inducing the expression of neurotrophic factors from the surrounding tissue [44, 45]. Transplanted MSCs also showed improved bone mineralization in mouse models of osteogenesis imperfecta and could be detected in a human patient suffering from the same disease after transplantation, indicating their potential as a possible therapeutic avenue for osteogenesis imperfecta [46, 47].…”
Section: In Utero Stem Cell Transplantation (Table 1)mentioning
confidence: 99%